Change in stage of presentation of head and neck cancer in the United States before and after the affordable care act. (August 2020) - Panth, Neelima; Barnes, Justin M.; Simpson, Matthew C.; Adjei Boakye, Eric; Sethi, Rosh K.V.; Varvares, Mark A.; Osazuwa-Peters, Nosayaba
Highlights: Overall, rate of early-stage HNC presentation remained unchanged. On the contrary, late-stage HNC increased post-ACA. Early-stage HNC presentation increased only among patients with Medicaid. Medicaid expansion may have impacted stage for low income patients. Abstract: Objective/Hypothesis: Early diagnosis and stage at presentation, two prognostic factors for survival among patients with head and neck cancer (HNC), are significantly impacted by a patient's health insurance status. We aimed to assess the impact of the Patient Protection and Affordable Care Act (ACA) on stage at presentation across socioeconomic and demographic subpopulations of HNC patients in the United States. Study Design: Retrospective data analysis. Methods: The National Cancer Database, a hospital-based cancer database (2011–2015), was queried for adults aged 18–64 years and diagnosed with a malignant primary HNC. The outcome of interest was change in early-stage diagnoses between 2011–2013 (pre-ACA) and 2014–2015 (post-ACA) using logistic regression models. Results: A total of 91, 137 HNC cases were identified in the pre-ACA (n = 53, 726) and post-ACA (n = 37, 411) years. Overall, the odds of early-stage diagnoses did not change significantly post-ACA (aOR = 0.97, 95 % CI 0.94, 1.00; p = 0.081). However, based on health insurance status, HNC patients with Medicaid were significantly more likely to present with early-stage disease post-ACA (aOR = 1.12, 95 % CI 1.03, 1.21; p = 0.007). We did not observe increased odds of early-stage presentation for other insurance types. Males were less likely to present with early-stage disease, pre- or post-ACA. Conclusions: We demonstrate a significant association between ACA implementation and increased early-stage presentation among Medicaid-enrolled HNC patients. This suggests that coverage expansions through the ACA may be associated with increased access to care and may yield greater benefits among low-income HNC patients.